Poor sleep and high rheumatoid arthritis risk: Evidence from large UK Biobank cohort - Yi-Qun Yang; Han-Wen Cao; Xing-Hao Yu; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (PLoS ONE, 2025)
Objective To evaluate the relationship between sleep behaviors and rheumatoid arthritis (RA) risk. Methods First, based on large-scale data from the UK Biobank, we analyzed the associations between multiple sleep factors and RA risk and calculated a poor sleep score (PSS) to assess their combined effect. Then we constructed genetic risk scores (GRS) based on a large genome-wide association study and assessed the interaction or combined effect of sleep and genetic factors on RA risk. Finally, we conducted a case-control study to explore the effect of RA on sleep. Results Sleep duration, getting up, napping during the day, insomnia, and daytime dozing were associated with the risk of RA, but no associations were observed for chronotype and snoring with RA. Participants in the high genetic risk and high PSS group had a 363.1% higher risk of developing RA compared to those with low genetic risk and low PSS. We also found that women were more likely than men to be affected by the combined effects of PSS and GRS. In the case-control study, there were statistically significant associations of RA with getting up, PSS grade and PSS. Conclusions Unhealthy sleep patterns were associated with increasing risk of RA among participants with low, intermediate, or high genetic risk.